Mekanisme Penagihan Utang Pajak Reklame Gagal Bayar Setahun di BAPENDA Situbondo - Arif Khisbul Waton (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This final project discusses the process of collecting overdue billboard tax in Situbondo Regency. The procedure begins with the issuance of a tax assessment letter, followed by a reminder phase. When payment is not fulfilled, the taxpayer receives up to three formal warnings, with penalties added at each stage. If noncompliance continues, the case is forwarded to the supervision and evaluation division, which initiates further action by issuing collection letters. Failure to respond to these demands leads to enforcement, including physical removal of the billboard. Several factors contribute to payment delays, such as lack of awareness, financial issues, and delayed approval processes with third parties. To improve compliance, the revenue office increases communication, provides education on tax responsibilities, and imposes firm sanctions to encourage timely payment. These strategies aim to optimize local revenue through effective and structured tax collection.
Entry oleh Arif 2026 Maret 16
Keywords: Reclame Tax; Mechanism; Enforcement; Delays; Compliance